2022
DOI: 10.3390/ijms232415829
|View full text |Cite
|
Sign up to set email alerts
|

FLIM of NAD(P)H in Lymphatic Nodes Resolves T-Cell Immune Response to the Tumor

Abstract: Assessment of T-cell response to the tumor is important for diagnosis of the disease and monitoring of therapeutic efficacy. For this, new non-destructive label-free methods are required. Fluorescence lifetime imaging (FLIM) of metabolic coenzymes is a promising innovative technology for the assessment of the functional status of cells. The purpose of this work was to test whether FLIM can resolve metabolic alterations that accompany T-cell reactivation to the tumors. The study was carried out on C57Bl/6 FoxP3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, T cells could be distinguished from tumor cells within the same tumor, where T cells had higher FAD and lower NAD(P)H mean lifetimes than tumor cells [124] . Another study tracked metabolic changes in T cells within the lymphatic nodes of melanoma-bearing mice over time as the tumor developed [125] . The authors detected an increase in unbound NADH ( α 1 ) and a decrease in protein-bound NADH ( α 2 ).…”
Section: Fluorescence Lifetime Imaging Microscopy (Flim) Of Nad(p)h A...mentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, T cells could be distinguished from tumor cells within the same tumor, where T cells had higher FAD and lower NAD(P)H mean lifetimes than tumor cells [124] . Another study tracked metabolic changes in T cells within the lymphatic nodes of melanoma-bearing mice over time as the tumor developed [125] . The authors detected an increase in unbound NADH ( α 1 ) and a decrease in protein-bound NADH ( α 2 ).…”
Section: Fluorescence Lifetime Imaging Microscopy (Flim) Of Nad(p)h A...mentioning
confidence: 99%
“…The authors detected an increase in unbound NADH ( α 1 ) and a decrease in protein-bound NADH ( α 2 ). This study applied a triple-exponential decay model to calculate the contribution of NADPH ( α 3 ) that was present only in the large tumor-bearing mice [125] . The changes in the NAD(P)H and FAD lifetime characteristics of tumor-associated T cells detected by these groups indicated a shift toward a glycolytic metabolism, consistent with prior work that identified a glycolytic phenotype in T cells [128] .…”
Section: Fluorescence Lifetime Imaging Microscopy (Flim) Of Nad(p)h A...mentioning
confidence: 99%
See 2 more Smart Citations
“…30 The mitosis process requires double cellular Compared with mitochondrial oxidative phosphorylation, aerobic glycolysis produces more NADPH and synthetic substrates and rapidly generates more ATP to satisfy the needs of proliferating cells. 31,32 GLUT1 is an important protein initiating cellular Glu uptake. It is reported that GLUT1 expression is upregulated in the psoriatic epidermis and correlated with the degree of acanthosis and the percentage of Ki-67 expression.…”
mentioning
confidence: 99%